DBSA-Catalyzed Sewage Sludge Conversion into Biodiesel in a CSTR: RSM Optimization and RTD Study - Ali A. Jazie (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Sewage sludge from the primary stage of a wastewater treatment plant (WWTP) in Al-Diwaniyah City was direct-transesterified to biodiesel using dodecylbenzenesulfonic acid catalyst in a system with two continuously stirred tank reactors. The response surface and the central cube design methodologies were used to optimize the parameters affecting the biodiesel yield. The optimum conditions for the process in this study were found to be (residence time: 90 min; catalyst loading 8 wt%; methanol/oil ratio: 18; reaction temperature: 368.15 K). Under the optimum process conditions a biodiesel yield of 96.51% was obtained. The experimental residence time distribution (RTD) was calculated and compartment models were applied for the two-tank reactor system. In the CSTR, a dead zone of (10 liter) was estimated. The independent analysis of fatty acids in the sewage showed that the lipids consisted primarily of palmitic acid (C16:0 = 37.86), oleic acid (C18:1 cis-9 = 19.72) and stearic acid (C18:0 = 17.32), and the acid value was (2.44 mg KOH/g). The properties of the biodiesel produced were comparable with the ASTM D-6751-2 standard and the properties of mineral diesel.